(untitled) (ACME, 2020)
This article directs attention toward two areas: on the one hand Latin literature, on the other the work of one of the most significant Italian contemporary poets. The purpose is to analyze male homoerotic motifs in Franco Buffoni’s poetry (b. 1948) in comparison with Latin poetry, in order to enlighten points of divergence and connection between classic and contemporary homoerotic poetry. It will be distinguished between homoerotic motifs, homoaffective motifs and homoclaiming ones; a further distinction will concern direct homoerotic quotations (from Catullus, Horatio, Lucretius, Vergilius) and an indirect presence of a homoerotic substratum. The final paragraph focuses on a comparison between homoerotic cycles: Buffoni’s Noi e loro (2008), Catullus’ Iuventius and Tibullus’ Maratus ones.